2006
DOI: 10.1080/10543400600760438
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Fungal Spores in a Cross-Sectional Study of Office Buildings

Abstract: Airborne fungal spores were measured in 44 office buildings in the summer and winter throughout the continental United States, as part of the Building Assessment, Survey and Evaluation (BASE) program. Six indoor air and two outdoor air samples were collected on a single day from each building. The cross-sectional and repeated measure design afforded evaluation of between-building and within-building variability of fungal spore levels in buildings. Total fungal spore concentrations in indoor air ranged from < 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…(20) The BASE study collected six indoor Burkard spore trap samples from each of 44 buildings and reported a median total concentration of 55 spores/m 3 and an intra-class correlation coefficient (ICC) of 0.57. (15) The median total spore concentration for samples collected on board the aircraft was 52 spores/m 3 , which was similar to the BASE study result even though the aircraft samples were collected during a single season (i.e., summer) and the BASE samples were collected during all four seasons.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…(20) The BASE study collected six indoor Burkard spore trap samples from each of 44 buildings and reported a median total concentration of 55 spores/m 3 and an intra-class correlation coefficient (ICC) of 0.57. (15) The median total spore concentration for samples collected on board the aircraft was 52 spores/m 3 , which was similar to the BASE study result even though the aircraft samples were collected during a single season (i.e., summer) and the BASE samples were collected during all four seasons.…”
Section: Discussionsupporting
confidence: 64%
“…(14) In many cases, mixed-effects modeling is used to analyze repeat measures from an individual, but it can also be applied to repeat measures from a sampling location. (15) The objectives of this research were to create a baseline of total fungi (culturable and total spore) concentrations on wide-body commercial passenger aircraft; test specific hypotheses on cabin location and different in-flight time periods; investigate the use of mixed-effects modeling techniques and covariance models; and estimate variability for total fungi in the aircraft environment.…”
Section: Introductionmentioning
confidence: 99%
“…These limited exposure assessment strategies do not accurately reflect the potential exposures of occupants because of temporal variability in airborne concentrations. MacIntosh et al 8 used a limited number of samples per day at each sample site to better understand the within-building variability. Although this was an important study in assessing spatial differences between regions of the continental United States, this study shows the diurnal and seasonal changes that can be expected during bioaerosol monitoring.…”
Section: Particulate Samplingmentioning
confidence: 99%
“…Airborne fungal concentrations may vary by season and environmental conditions. 8 MacIntosh et al 8 assessed building-to-building variability in airborne concentrations of fungal spores through the use of Burkard spore traps at 44 office buildings across the United States as a part of the Building Assessment, Survey, and Evaluation (BASE) study. Their sampling strategy consisted of three short-term (4-min) indoor samples and one outdoor sample in both the morning and afternoon.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies regarding to indoor microbiological air quality have been conducted [9][10][11][12][13]. However, the data of the assessment of indoor microbial contamination in Malaysia or other Southeast Asian countries which share common hot and humid climate was very limited [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%